2018
DOI: 10.1590/s0100-83582018360100032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Weeds as Virus Reservoirs in Watermelon Crops

Abstract: -Watermelon is one of the most important vegetable crops in Brazil, which is grouped among the greatest producers worldwide. Viruses stand out among the most damaging disease agents, which can drastically reduce fruit production. In this context, weeds present in the field can also interfere in crop production, acting as reservoirs for viruses. Thus, this study aimed to investigate virus occurrence in weeds at the main watermelon-growing regions in the State of Tocantins. Viruses identification (e.g. potyvirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…The ecology of begomoviruses identified by HTS studies in non-cultivated plants requires more effort in order to understand the contribution of these plants for disease development [74,75,76]. Non-cultivated plants could be a source of viral inoculum to cultivated plants [77,78,79,80,81,82,83] and could contribute to viral evolution. Here, we described some non-cultivated plants at the agro-ecological interface carrying geminivirus-signatures (Table 3 and Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…The ecology of begomoviruses identified by HTS studies in non-cultivated plants requires more effort in order to understand the contribution of these plants for disease development [74,75,76]. Non-cultivated plants could be a source of viral inoculum to cultivated plants [77,78,79,80,81,82,83] and could contribute to viral evolution. Here, we described some non-cultivated plants at the agro-ecological interface carrying geminivirus-signatures (Table 3 and Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, a study observed the interactions between P. angulate and several cucurbit viruses, including watermelon mosaic virus and zucchini yellow mosaic virus. It was revealed that this weed was a host of several viruses, and served as a secondary source of infection for cucurbits [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability of these weeds, and others that are known hosts, to successfully transmit the virus to other Cucurbitaceae hosts has not been well documented. Previous research in Brazil in watermelon growing regions has identified several weeds, including A. spinosus , P. angulate, and Heliotrpoium indicum , as potential reservoirs for viruses of a range of genera, including potyviruses, cucumoviruses, and orthotospoviruses [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, PRSV-W was detected in 22% of symptomatic plants by ELISA method, while mRT-PCR found it in 75% (Table 2). It is worth mentioning that weeds can act as natural reservoirs of these watermelon viruses, particularly ZYMV and PRSV-W (Aguiar et al, 2018). The distribution of virus in the state can be attributed to the mode of transmission, nonpersistent by several species of aphids, of these viruses (CMV, PRSV-W, WMV, and ZYMV).…”
Section: Discussionmentioning
confidence: 99%